Dual treatment of cutaneous leishmaniasis with topical amphotericin B and photodynamic therapy in a pediatric patient. Issue 5 (30th May 2022) - Knapp, Calvin; Vaz, Louise; Onoday, Heather; Small, Alison
Abstract: Cutaneous leishmaniasis is a parasitic infection that can result in scarring, contributing to significant morbidity when a cosmetically sensitive area is involved. We report a case of a 13‐year‐old boy with cutaneous leishmaniasis involving the face and arm. He was treated with a combination of photodynamic therapy as well as topical amphotericin with a cosmetically satisfying outcome. This combination of noninvasive treatment regimens has not been reported to our knowledge and merits further study in the pediatric population.